Klinische Sportmedizin - Ferger K; Moritz C (Deutsche Zeitschrift für Sportmedizin, 2017)
Introduction: In recent years static stretching has taken center stage in selected sports science discussions. Several studies show that especially static stretching has a short-term negative effect on directly-following maximum and speed-strength performance. This study makes a selected contribution to the use of suitable compensating exercises immediately after static stretching that produce the baseline output. Methods: This research reviewed two already proved and tested compensating exercises in terms of their effectivity inthe testparameter Squat-Jump and a new exercise was also generated. For this,21 participants were split into three experimental groups. The subsequentevaluation based on forming hypotheses in which the analysis of variance with repeated measures was used as significance test.Results: In all experimental groups,a static stretching induced a significant reduction (DL: 6.92%; EK: 6.6%; MS: 6.24%) and a following compensating exercise a significant increase (DL: 7.87%; EK: 6.07%; MS: 5.29%) of the jump height. Only a 10-minute run was able to restore baseline performance and furthermore overcompensate the jump height. The other experimental groups stayed closebelow their baseline performance.Discussion: The topic static stretching and compensating exercises still shows numerous structural options (intensity, repetition, durationetc.) with different effects and results, which make it difficult to make comparative and individual, as well as practical statements. In general,one can say that static stretching should be avoidedor appropriate compensating exercises must be performed whenever highest maximum and speed-strength performances are necessary. KEY WORDS: Stretching, Compensation, Squat-Jump, Maximum Strength